Degradabilidade in situ do Capim Panicum maximum cv. Tanzânia Incubado Cortado ou na Forma de Extrusa - Salman, AKD; Berchielli, T. T.; da Silveira, R. N.; Soares, WVB; Nogueira, JR; Kronka, S. N. (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2000)
The aim of this study was to compare the chemical composition, in vitro dry matter disappearance (IVDMD) and ruminal degradation of Panicum maximum, J. cv. Tanzania samples obtained by clipping (square method) or extrusa collection (animal selection). In the in situ trial, three ruminal fistulated dry crossbred cows, with 499 kg LW, were used in a completely randomized block design with split-plot arrangement design. Five grams of clipped (+/- 2 cm) grass or extrusa samples were placed in nylon bags (7 x 14 cm) and rumen incubated during 3, 6, 12, 24, 48, 96 and 120 hours. The IVDMD and the CP, NDF and ADF content were, respectively, 55.8, 7.6, 81.9 e 43.6%, for the clipped grass and .66.5, 12.1, 78.8 e 39.5%, for the extrusa samples. The potential degradability of DM, C P, NDF and ADF were 62.59, 80.88, 50.73 and 46.65%, for clipped grass; and 79.53, 90.97, 71.21 and 65.68%, for extrusa samples. The quality of the selected animal diet (extrusa) was better than the available forage in terms of IVDMD and chemical composition (high protein and low fiber content). In situ degradability trials carried out with clipped samples, and non selected by animal, could not supply reliable results closed to the animal diet.
In situ degradability of clipped or extrusa samples of Panicum maximum cv. Tanzania
Keywords: in situ degradability; In vitro digestibility; ruminant